SALURAN PEMASARAN DAN MARJIN PEMASARAN TANAMAN KRATOM DI DESA TELUK SINDUR KECAMATAN BIKA KABUPATEN KAPUAS HULU - Juliana Eva; Emi Roslinda; Sudirman Muin (Forestry Study Program University Of Mataram, 2024)
The purpose of this study was to explain the marketing channel of kratom leaves in Teluk Sindur Village, Bika District, Kapuas Hulu Regency, calculate the marketing margin of kratom leaves in Teluk Sindur Village, Bika District, Kapuas Hulu Regency and calculate the marketing efficiency (farmer share) of kratom leaves in Teluk Sindur Village, Bika District, Kapuas Hulu Regency. The method used in collecting research data is the survey method, for the research sampling method of kratom leaf producers is done randomly (Random Sampling). The results showed that kratom marketing from Teluk Sindur Village, Bika District, Kapuas Hulu Regency had three marketing channels, namely: Channel I has three levels, from farmers to pengempul traders, pengempul traders to large traders, large traders to retailers, then retailers to consumers. Channel II has two levels, from farmers to collectors, collectors to retailers, retailers to consumers. Channel III has no levels, which only consists of farmers to consumers. Kratom marketing margins are still said to be inefficient with the results obtained, namely: channel I of Rp 59,834/kg channel II of Rp 45,000/kg and channel III of Rp 50,000/kg. Kratom marketing efficiency is efficient and not yet efficient, seen from the value of farmer share in marketing channel I of 22.22%, marketing channel II of 34% and marketing channel III of 100%.